Integrated mRNA and microRNA expression analysis of root response to phosphate deficiency in Medicago sativa - Li, Zhenyi; Tong, Zongyong; He, Feng; Li, Xianglin; Sun, Juan (Frontiers in Plant Science, 2022)
The deficiency of available phosphate significantly limits plant growth and development. This study sought to investigate how alfalfa (Medicago sativa), a high-yielding and high-quality forage widely cultivated worldwide, responds to phosphate deficiency stress by integrating transcriptional and post-transcriptional data. In this study, 6,041 differentially expressed genes (DEGs) were identified in alfalfa roots under phosphate deficiency conditions. Furthermore, psRNATarget, RNAhybrid, and TargetFinder were used to predict the target genes of 137 differentially expressed miRNAs (DEMs) in the root. In total, 3,912 DEGs were predicted as target genes. Pearson correlation analysis revealed 423 pairs of miRNA-mRNA regulatory relationships. MiRNA negatively regulates mRNA involved in regulatory pathways of phosphate deficiency responses in alfalfa. miR156e targeted squamosa promoter-binding-like protein 13A (SPL13), miR160c targeted auxin response factor 18 (ARF18), and miR2587a controlled glycolysis and citrate cycle via Phosphoenolpyruvate carboxykinase (ATP) (PCKA). Novel-miR27 regulated SPX domain-containing protein that controls phosphate transport in alfalfa root, novel-miR3-targeted sulfoquinovosyl transferase SQD2 controlled sulfolipid synthesis and glutathione S-transferase (GST) (mediated by miR169j/k and novel-miR159) regulated glutathione metabolism. miR399l regulated auxin-responsive protein SAUR72 involved in IAA signal transduction, while abscisic acid receptor PYL4 (regulated by novel-miR205 and novel-miR83) participated in ABA signal transduction. Combined miRNA-mRNA enrichment analysis showed that most miRNAs regulate the phosphate starvation response of alfalfa by modulating target genes involved in carbohydrate metabolism, sulfolipid metabolism, glutathione metabolism, and hormone signal transduction. Therefore, this study provides new insights into the post-transcriptional regulation mechanism of phosphate deficiency responses and new perspectives on phosphate assimilation pathways in alfalfa and other legumes.